Poetry Out Loud: Two Perspectives, The Halls Come Alive With the Sound of Poetry - Thebedeau, Susan (Maine Policy Review, 2015)
Poetry Out Loud, a national poetry recitation contest begun by the National Endowment for the Arts and the Poetry Foundation in 2006, is described from two perspectives. This short article is by a Bangor High School English teacher who coordinates her school’s program.